The Consuming soy flour after weight training: An alternative to increase leg muscle strength - Wilda Welis; Rully Effendi; Deby Tri Mario; Ilham Ilham; Nurul Ihsan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The aim of this study was to find out whether soybean flour and lunge training can have a significant effect on muscle strength. This research method is a pre-test-post-test design (quasi-experiment). Using a total sampling technique, 14 Indonesian PPLP West Sumatra Pencak Silat athletes were used as research samples. The research procedure included measuring muscle strength (leg dynamometer) before administering 29g protein after lunges training (pre-test). Then the treatment was given in 16 meetings, with a frequency of 2 sessions per week for 8 weeks. The intensity of the training/intervention given was submaximal (80% to 90% of maximum capacity). Giving soy flour to athletes 30 minutes after training is in accordance with the protein requirements given to athletes in each session, namely 29 grams of protein equivalent to 73 grams of soy flour with the addition of 1 tablespoon of granulated sugar and 200 ml of water. The results of statistical tests using the t test showed that testing the data resulted in (p<0.05) a percentage increase of 6.91%. In conclusion, adding protein supplementation to support weight training can increase muscle strength. Planned, structured and consistent exercise is necessary for any protein supplement to work. The use of this protein supplement must be adjusted to the needs of each participant to get the best preparation results. The findings of this research can be used by athletes who want to or are currently implementing a training program, as well as coaches as evaluation material, and nutritionists as material experts.